Exploring the potential of Bacillus for crop productivity and sustainable solution for combating rice false smut disease - Pandey, Neha; Vaishnav, Richa; Rajavat, Asha Singh; Singh, Arvind Nath; Kumar, Sanjay; Tripathi, Ravi Mani; Kumar, Madan; Shrivastava, Neeraj (Frontiers in Microbiology, 2024)
Rice False Smut is caused by the soil-borne fungal pathogen Ustilagonoidea virens (U. virens), which is one of the most threatening diseases in most of the rice growing countries including India, that causes 0.5-75% yield loss, low seed germination and reduction in seed quality. The assessment of yield loss helps to understand the relevance of disease severity and allows appropriate management strategies to be implemented. This study aimed to mitigate biotic stress in rice by employing rhizobacterial based bioformulation which possess multifarious ability as plant growth-promoting and biocontrol potential against U. virens. Rhizobacteria were isolated from the soil of the rice rhizospheres from the healthy plant of false smut affected zone. Further, they were identified as Bacillus strains; B. subtilis (BR_4), B. licheniformis (BU_7), B. licheniformis (BU_8), and B. vallismortis (KU_7) via sequencing. Isolates were screened for their biocontrol potential against U. virens under in-vitro conditions. The antagonistic study revealed B. vallismortis (KU_7) inhibited U. virens the most (44.6%) followed by B. subtilis BR_4 (41.4%), B. licheniformis BU_7 (39.8%) and B. licheniformis BU_8 (43.5%). Various biochemical and plant growth promotional attributes, like phosphate & Zn solubilization, IAA, ammonium, siderophore, and chitinase production, etc. were also checked for all the selected isolates. Further, the potential of the isolates was tested in both in vitro and field conditions employing talc-based bioformulation by bio-priming and the root treatment. Application of bioformulation revealed a 20% decrease in disease incidence in plants treated with B. vallismortis (KU_7), 60.5% increase in the biological yield and a 45% increase in the grain yield. This ecofriendly approach not only suppressed the disease but also improved grain quality and reduced the chaffiness.